Techno-economic assessment and strategic proposal for designing and optimizing the required powered battery for an electric motorcycle under varying driving cycle tests - Do, Tan-Thich; Dinh, Tan-Ngoc; Ly, Vinh-Dat (International Journal of Renewable Energy Development, 2025)
Recently, many countries have committed to achieving net-zero emissions by 2050, making the adoption of electric motorcycles increasingly significant. The expansion of electric motorcycles has gained popularity due to their affordability, ease of use, and environmental benefits. In the design of electric motorcycles, optimizing energy efficiency and economic viability both technologically and economically is a key consideration. This study focuses on developing a mathematical model and strategic proposal with the step-by-step calculation for determining the required power battery for electric motorcycles under various driving cycle tests, implemented using Matlab software. The results analyze and discuss the effects of operating conditions on the electric motorcycle’s dynamic performance, average energy consumption, and battery cell and pack characteristics. Ultimately, the battery pack optimization strategy was proposed and conducted using the Mixed-Integer Linear Programming (MILP) approach. As a result, the Toshiba battery trademark was identified as the optimal choice for the required power battery in the electric motorcycle, considering both technological effectiveness and economic factors. The Toshiba battery pack has a capacity of 39 Ah, 17 cells, a mass of 13.94 kg, and a cost of $459, respectively. After designing and optimizing the required battery pack for the electric motorcycle, the model was validated to ensure that the pack’s energy exceeds the average energy consumption under varying driving cycle tests. Therefore, the model demonstrates high reliability. This study provides valuable insights into designing and evaluating the dynamic performance and battery pack characteristics of electric motorcycles.